Effect of Plant Growth Regulator Fungicide and ABA on Growth and Biochemical properties of Basella alba Linn - Alagu Lakshmanan, Ganapathy M (International Journal of Pharmaceutical & Biological Archive, 2012)
Effect of Plant Growth Regulator Fungicide and ABA on Growth and Biochemical properties of Basella alba Linn